Facile synthesis of reusable graphene oxide composite magnetic beads for removal of arsenic (III) - Savan K. Raj; Jeet Sharma; Vaibhav Kulshrestha (SPE Polymers, 2021)
Abstract Consumption of As(III) in drinking water is a severe problem, and more than 180 million people are suffering worldwide. Therefore, developing an affordable technique to remove As(III) from drinking water is essential to protect human health. In this work, we report chitosan‐iron oxide‐graphene oxide composite beads (GO‐BDs) for the removal of As(III) from the drinking water. The incorporation of chitosan and graphene oxide (GO) provides better physical strength and stability to the GO‐BDs. Prepared GO‐BDs were characterized using different characterization techniques. X‐Ray diffraction (XRD) spectra show the iron oxide nanoparticles were successfully linked with graphene oxide. The size of the beads confirmed by scanning electron microscopy (SEM) and found to be ~1 mm. Elemental mapping of beads show the uniform dispersion of GO/iron oxide on the surface of the beads. The adsorption of As(III) occurs rapidly and attain equilibrium condition in <6 h after removing As(III) from the water within the permissible limit. Effect of water pH, time, temperature, adsorbent dosage, and concentration of the dose have been studied in detail for arsenic removal. Coexisting ions show negligible influence on As(III) removal. Langmuir and Freundlich isotherms were also examined. This study provides the application of GO‐BDs for As(III) removal from contaminated drinking water.